QUANTIFICATION OF ROPINIROLE HYDROCHLORIDE IN API AND TABLETS BY NOVEL STABILITY-INDICATING RP-HPLC METHOD: IT’S VALIDATION AND FORCED DEGRADATION STUDIES - R., SADASHIVAIAH; G., Rohith; B. K., SATHEESHA BABU (International Journal of Applied Pharmaceutics, 2019)
Objective: A simple, economical, robust and stability-indicating reverse phase high performance liquid chromatography method was developed and validated for the quantification of ropinirole hydrochloride in API and tablets to achieve shorter retention time, to minimize human error by avoiding the use of buffers and weighing procedure and analyze more number of samples in shorter period of time with good accuracy. Methods: The chromatographic conditions for separation of ropinirole hydrochloride was carried out using Gemini NX C18 column (15 cm x 4.6 mm), 5 µm particle size with the mobile phase composing of methanol: acetonitrile (70:30 v/v), delivered at flow rate 0.7 ml/min and UV detection wavelength at 250 nm. Results: The retention time was observed at 2.718 min. The system suitability results were found to be within limits. The method was precise, with lower than 2 %RSD and the calibration curve was linear (r2=1) over a concentration range of 2.5-160 µg/ml. The detection and quantification limit was found to be 0.045 µg/ml and 0.15 µg/ml, respectively. Recovery of the drug was found between 100.09-100.19%. The assay of ropinirole hydrochloride in ROPITOR® and ROPARK® tablets were found to be 100.4 and 103.60 %, respectively. The forced degradation studies were carried out to demonstrate the specificity of the method by exposing the API under conditions of hydrolysis, oxidation, thermal and photolytic as per ICH Q1A(R2) guidelines. Conclusion: The low coefficient of variation and agreeable recovery confirmed that the newly developed method could be employed for routine analysis of ropinirole hydrochloride in API and tablets.